2007
DOI: 10.2466/pr0.100.3.803-809
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors in Perceived Unwanted Transparency

Abstract: The feeling experienced when another person seemingly notices something about them that they would rather conceal from others is referred to as a sense of unwanted transparency. Effects of perception of others on one's sense of unwanted transparency were investigated. Participants, after being led to believe that they had performed poorly on an important ability test, interacted with an instructor who was apparently unaware of their poor performance. Participants' perception of the instructor was manipulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These findings provide hints about the sense of unwanted transparency, the sense experienced when another person appears to notice something during an interaction that one would rather not have noticed (Tabata, 2007(Tabata, , 2008(Tabata, , 2009). Tabata (2008) suggested that silent pauses and aversion of gaze arising from the sense of unwanted transparency may not feel natural to the viewer.…”
Section: Discussionmentioning
confidence: 80%
“…These findings provide hints about the sense of unwanted transparency, the sense experienced when another person appears to notice something during an interaction that one would rather not have noticed (Tabata, 2007(Tabata, , 2008(Tabata, , 2009). Tabata (2008) suggested that silent pauses and aversion of gaze arising from the sense of unwanted transparency may not feel natural to the viewer.…”
Section: Discussionmentioning
confidence: 80%
“…The feeling experienced during a social interaction by a person when another seemingly notices something about the person that he would rather conceal has been defined as the sense of unwanted transparency (Tabata, 2007). It has been suggested that most people experience the sense of unwanted transparency (Tabata & Yoshida, 2008).…”
mentioning
confidence: 99%
“…It has been suggested that most people experience the sense of unwanted transparency (Tabata & Yoshida, 2008). Several studies investigating the concept have mainly focused on two aspects: factors associated with the intensity of the sense of unwanted transparency (e.g., Tabata, 2006Tabata, , 2007 and responses arising from the sense of unwanted transparency (e.g., Tabata, 2008). It has been proposed that self-focused attention (Tabata, 2006) and perceptions of others (Tabata, 2007) may affect the intensity of the sense of unwanted transparency.…”
mentioning
confidence: 99%